Comparative analysis of the refraction of microwaves at different frequencies in an inhomogeneous plasma of a high power impulse reflex discharge - Kovtun, Yu.V.; Siusko, Y.V.; Skibenko, E.I. (Вопросы атомной науки и техники, 2018)
The trajectories of microwave rays at 36 and 71 GHz frequencies are calculated. A time dependences of an amplitude of scattered microwave signals at 36 and 71 GHz frequencies are experimentally measured. A comparison and analysis of experimental and calculated data, which are in satisfactory agreement, has been carried out.